Glutathione peroxidase 4 and vitamin E cooperatively prevent hepatocellular degeneration - Carlson, Bradley A. (Redox Biol, 2016)
The selenoenzyme glutathione peroxidase 4 (Gpx4) is an essential mammalian glutathione peroxidase, which protects cells against detrimental lipid peroxidation and governs a novel form of regulated necrotic cell death, called ferroptosis. To study the relevance of Gpx4 and of another vitally important selenoprotein, cytosolic thioredoxin reductase (Txnrd1), for liver function, mice with conditional deletion of Gpx4 in hepatocytes were studied, along with those lacking Txnrd1 and selenocysteine (Sec) tRNA (Trsp) in hepatocytes. Unlike Txnrd1- and Trsp-deficient mice, Gpx4(−/−) mice died shortly after birth and presented extensive hepatocyte degeneration. Similar to Txnrd1-deficient livers, Gpx4(−/−) livers manifested upregulation of nuclear factor (erythroid-derived)-like 2 (Nrf2) response genes. Remarkably, Gpx4(−/−) pups born from mothers fed a vitamin E-enriched diet survived, yet this protection was reversible as subsequent vitamin E deprivation caused death of Gpx4-deficient mice ~4 weeks thereafter. Abrogation of selenoprotein expression in Gpx4(−/−) mice did not result in viable mice, indicating that the combined deficiency aggravated the loss of Gpx4 in liver. By contrast, combined Trsp/Txnrd1-deficient mice were born, but had significantly shorter lifespans than either single knockout, suggesting that Txnrd1 plays an important role in supporting liver function of mice lacking Trsp. In sum our study demonstrates that the ferroptosis regulator Gpx4 is critical for hepatocyte survival and proper liver function, and that vitamin E can compensate for its loss by protecting cells against deleterious lipid peroxidation.